3D propagation of the shock-induced vibrations through the whole lower-limb during running. (11th November 2019) - Chadefaux, D.; Gueguen, N.; Thouze, A.; Rao, G.
Abstract: Shock-induced vibrations to the feet have been related to the feel of comfort, the biomechanical control of performance, and the risk of fatigue or injury. Up to recently, the complexity of measuring the human biodynamic response to vibration exposure implied to focus most of the research on the axial acceleration at the tibia. Using wireless three-dimensional accelerometers, this paper investigates the propagation of shock-induced vibrations through the whole lower-limb during running in the temporal and the spectral domains. Results indicated that the vibrations were not consistent across the lower-limb, showing various spatial and spectral distributions of energy. The amount of energy was not constantly decreasing from the distal to the proximal extremity of the runner's lower-limb, especially regarding the lateral epicondyle of the femur. Vibrations in the transversal plane of the segments were substantial compared to the longitudinal axis regarding the distal extremity of the tibia, and the lateral epicondyle of the femur. Further, the spectral content was wider at the distal than at the proximal end of the lower-limb. Finally, to get a thorough understanding of the risks incurred by the runners, the need to account for shock-induced vibrations up to 50 Hz has been stressed when investigating three-dimensional vibrations. The overall study raises attention on the substantial importance of the transverse components of the acceleration, and their potential relation to shear fatigue and injury during running.